Quasi-static unfolding mechanics of a creased membrane based on a finite deformation crease–beam model. (15th December 2020) - Xia, Z.M.; Wang, C.G.; Tan, H.F.
Graphical abstract: Abstract: This paper studies the unfolding mechanical behavior of a creased membrane with different crease characteristics under tensile load. The three-dimensional unfolding shape measured by a noncontact test system reflects both panel bending and crease opening. The rotational stiffness of the crease can be characterized based on the test shape. A finite deformation crease–beam model is developed to describe this unfolding mechanism. The predicted results show that the unfolding behavior of the creased membrane is affected by the ratio of the rotational stiffness of the crease to the bending stiffness of the panel. Analysis of the unfolding mechanism for the creased membrane reveals the contributions of three deformation styles—namely panel bending, panel tension, and crease opening—during different unfolding stages. The present results can be used to guide the controllable unfolding of crease-based deployable structures by adjusting the crease characteristics.